The ATPase Inhibitory Factor 1 is a Tissue-Specific Physiological Regulator of the Structure and Function of Mitochondrial ATP Synthase: A Closer Look Into Neuronal Function - Domínguez-Zorita, Sonia; Romero-Carramiñana, Inés; Cuezva, José M.; Esparza-Moltó, Pau B. (Frontiers in Physiology, 2022)
The ATP synthase is an essential multifunctional enzyme complex of mitochondria that produces most of cellular ATP, shapes the structure of the inner membrane into cristae and regulates the signals that control cell fate or demise. The ATPase Inhibitory Factor 1 (IF1) functions in vivo as a physiological regulator of the ATP synthase and thereby controls mitochondrial structure and function, and the retrograde signaling pathways that reprogram nuclear gene expression. However, IF1 is not ubiquitously expressed in mammals, showing tissue-restricted expression in humans and mice and large expression differences between the two species in some tissues. Herein, we summarized key regulatory functions of IF1 for tissue homeostasis, with special emphasis on the deleterious effects that its genetic ablation in neurons has in learning. The development and characterization of tissue-specific mouse models with regulated expression of IF1 will be crucial to disentangle the contribution of the ATP synthase/IF1 axis in pathophysiology.